Steering thermal photoassociation of magnesium atoms by two time-delayed femtosecond laser pulses - Zhang, Rong; Hu, Jin-Wei; Han, Yong-Chang; Fu, Bina; Shundalau, Maksim (Frontiers in Physics, 2023)
By solving the full-dimensional time-dependent Schrödinger equation with the thermal-random-phase wavepacket method, we investigate the photoassociation (PA) process of hot (1000 K) magnesium atoms induced by two time-delayed femtosecond laser pulses. Driven by the 840 nm femtosecond laser pulses, the Mg_2 molecules can be formed on the four excited states, (1)^1Π_g, (1)^1Π_u, (2)^1Π_u, and (2)^1Σ^+_u, from the initial electronic ground state X^1Σ^+_g. It is found that the three-photon couplings between X^1Σ^+_g and the three ungerade states ((1)^1Π_u, (2)^1Π_u, and (2)^1Σ^+_u) play dominant roles in the population transfer process. By scanning the pulse duration τ from 50 to 200 fs, and varying the delay time δ t_0 from 0 to 2 τ fs, we find that the final PA population is strongly dependent on the two parameters. For a given δ t_0, the parameter τ can induce a significant variation (26.8 times) for the final PA population transfer, and for a given τ, one can also obtain a significant variation (2.73.5 times) of the final PA population by varying δ t_0. Additionally, the dynamics of the coherently vibrational wavepackets of the four excited states are also influenced by the two parameters.